A STUDY TO ASSESS THE EFFECTIVENESS OF LACTATION COUNSELING ON MATERNAL AND NEONATAL OUTCOMES AMONG PRIMIPARA MOTHERS ADMITTED IN SELECTED PRIMARY HEALTH CENTER AT ERODE DISTRICT (CAHIERS MAGELLANES-NS, 2024)
Aim: To assess the effectiveness of lactation counseling on maternal and neonatal outcomes among primipara mothers admitted in selected primary health center at Erode District. Methods: Quantitative Research Approach with One group pre-test post-test Design. the sample size is 60 primipara mothers, using Simple random sampling technique (lottery method). The study was conducted by adopting a one group pre test post test design. The study was carried out with 60 primipara mothers who fulfilled the inclusion criteria. Simple random sampling technique (Lottery Method) was used to select the primipara mothers. The investigator introduced herself to the mothers and explained the purpose of the study to ensure cooperation. After conducting pretest, the planned training programme 30 to 45 minutes was given for primipara mothers by using various devices like flash cards, video clips, and demonstration with dummy doll. On 2nd day Mother to Mother Demonstration 15 to 20 minutes, as a group (3 to 5mothers). The investigator was conducting the posttest by using the same standardized tools, for primipara mother on the 3rd day.Results: The significant difference between pretest and posttest mean score of the neonatal outcome. The pretest level of mean score was 10.183 with the standard deviation of 3.357 and the posttest level of mean score was 15.167 with the standard deviation of 3.613. The paired‘t’ test value was 15.872 at the level of p<0.05. Which indicates the lactation counseling can make high neonatal outcome regarding breast feeling among primipara mothers.Conclusion: Therefore, investigator felt that, more importance should be given in educating and practicing the primipara mothers was effective improving the awareness regarding breast feeding. So there was a significant difference in the level of knowledge and practice after giving training programme regarding breast feeding.